2017
DOI: 10.15446/rsap.v19n4.39597
|View full text |Cite
|
Sign up to set email alerts
|

Actividad en suero de CK y CK-MB en pacientes con infección por el virus dengue

Abstract: In this study, no patient with dengue infection had heart disease or myositis; however, the finding of a higher frequency of elevated level CK and CK-MB in the dengue patients compared to the control group suggests the involvement of the striated muscle and of the cardiac muscle in this group. For this reason, the monitoring of these enzymes should be considered as part of the monitoring of patients with dengue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The first case of sinus node dysfunction related to dengue infection was reported in a threeyear-old boy who developed hypotension and bradycardia after recovering from dengue hemorrhagic fever [25]. Agudelo-Salas et al reported that in patients without a myocarditis diagnosis, a significant presence of symptoms may suggest its presence, including tachycardia (23.1%), bradycardia (15.4%), and hypotension (12.8%) [26]. As previously stated, the cardiac effects of dengue virus extend beyond myocarditis, and can affect the conduction system, including nonspecific ST-segment alterations and low QRS complex voltage, in addition to the arrhythmias previously described.…”
Section: Cardiac Manifestationsmentioning
confidence: 99%
“…The first case of sinus node dysfunction related to dengue infection was reported in a threeyear-old boy who developed hypotension and bradycardia after recovering from dengue hemorrhagic fever [25]. Agudelo-Salas et al reported that in patients without a myocarditis diagnosis, a significant presence of symptoms may suggest its presence, including tachycardia (23.1%), bradycardia (15.4%), and hypotension (12.8%) [26]. As previously stated, the cardiac effects of dengue virus extend beyond myocarditis, and can affect the conduction system, including nonspecific ST-segment alterations and low QRS complex voltage, in addition to the arrhythmias previously described.…”
Section: Cardiac Manifestationsmentioning
confidence: 99%